(untitled) (Revista Científica Integrada, 2023)
Objective: To build a specialized nursing terminology for the care of elderly people with mental suffering, within the scope of primary care, using the International Classification for Nursing Practice (ICNP®) version 2019/2020. Method: A methodological study carried out in three stages: 1) Identification of terms from the professional nursing language about elderly people with mental suffering, in the context of primary care; 2) Cross mapping of terms identified with ICNP® terms and 3) Classification of identified terms according to the ICNP® 2019/2020 Seven Axis Model. Results: 2,958 terms were extracted and then the selection process was carried out, which resulted in 100 terms, which were mapped with the ICNP® and analyzed according to the degree of equivalence, thus identifying 66 (66%) terms contained in the ICNP ® 2019/2020, 44(44%) with equivalence degree 1 and 22(22%) with equivalence degree 2; and 34(34%) terms not included in this classification, with 5(5%) equivalence degree 3, 10(10%) with equivalence degree 4, and 19(19%) with equivalence degree 5. Conclusion: Constructed a specialized nursing terminology with terms considered, clinically and culturally, relevant to the clinical practice of nursing with elderly people in mental distress.